Application of bibliometrics indicators in assesments the value of researchers: Simion Băncilă, Pavel Topală, Eugen Plohotniuc, Mihai Popa (Confluenţe Bibliologice, 2013)
This paper presents the results of an investigation conducted to estimate the value of the results of scientiﬁc researches of four teachers from the Faculty of Science, Economics and the Environment through scientometric measuring. The quantity and quality indicators have been using: the total number of publications, the language of publications, a variety of documents, participation in scientiﬁc events, the number of citations, implementation of the results achieved in the economy. The contribution of the Scientiﬁc Library is revealed in the aﬃrmation of the teachers-researchers at the Balti University.
Keywords: scientometrics; scientiﬁc research; scientiﬁc contributions; Popa Mihail (1968); Plohotniuc Eugeniu (1953); Topală Pavel (1958); Băncilă Simion (1941 -2024)